Acute and session RPE responses during resistance training: Bouts to failure at 60% and 90% of 1RM - Pritchett, RC; Green, JM; Wickwire, PJ; Kovacs, MS (South African Journal of Sports Medicine, 2009)
Objective. To compare resistance bouts performed to failure at low (60% 1RM) and high (90% 1RM) workloads for acute rate of perceived exertion (RPE) (per exercise), session RPE (S-RPE) (30 min post), HR (per exercise) and total work (per session, and per exercise). Background. RPE is a convenient method for quantifying intensity in aerobic exercise. However, RPE has recently been extended to exercise modalities dominated by anaerobic pathways such as resistance training (RT). Method. Subjects (N=12) were assessed using an exercise-specific 1 repetition maximum (1RM) for 6 exercises. On separate days in a counterbalanced order, subjects performed 3 sets of each exercise to volitional failure at a low intensity (LI) and a high intensity (HI) with 2 minutes rest between sets and exercises. At the end of each set, subjects estimated acute RPE for that set using a 10-point numerical scale. Thirty minutes after the end of the exercise session subjects estimated their S-RPE for the entire workout. HR, total work, and acute RPE were compared (HI v. LI) using repeated measures ANOVA. Results. A paired samples t-test showed LI was significantly higher (p=0.039) than HI for session RPE (LI=8.8±0.8, HI=6.3±1.2) and total work (LI=17461±4419, HI=8659±2256) (p=0.043). Per exercise, total work and acute RPE were significantly greater (p=0.01) for LI for all exercises. Peak HR was significantly higher per exercise during LI for leg press (p=0.041), bench press (p=0.031), lat pull-down (p=0.037) and shoulder press (p=0.046).